Peningkatan Kemampuan Membuat Petunjuk Penggunaann Alat Peraga Menentukan Luas Daerah Bangun Datar Kepada Para Guru SD Di Kecamatan Labuapi - Ketut Sarjana; Muhammad Turmuzi; Nani Kurniati; Nurul Hikmah; Ratna Yulis Tyaningsih (Pascasarjana Universitas Mataram, 2021)
Elementary school teachers in labuapi group II have never made instructions for the use of props. Do not use instructions, props alone have never been made. Knowledge of the manufacture of props and instructions are very poorly obtained and the opportunity to learn is also minimal. The objectives to be achieved in this devotional activity are: (1) Improving the knowledge of the teachers of SD Cluster II in Labuapi Subdistrict about the concept of area area and the principle of area area can be built through the concept of broad immortality; (2) Improve the skill of making instructions for using props to determine the area of data building. Devotion activities are carried out through the deepening of the concepts and principles of the area, especially the parameters of determining the area by means of presentation, demonstration, simulation and practice of designing a broad principle model media, and discussions in working groups and presentations about the media and guidelines that have been designed and demontrasi how it is used. The training results are very effective, this is shown to be a significant average difference between pretest and post-test results. Community Service activities that have been conducted turned out to be very effective, namely a change towards significant improvement. This can be shown by the difference in the pre-test average of 4.08 with a post-test average of 7.35. The test result t shows that = 15,286 > ttab = 2.03 at the signification level of 5 %. This also means that knowledge of the area of flat build area and the skills of designing media and operational guidelines of teachers in Cluster II Labuapi Subdistrict increased convincingly as shown by the average change